Consultant's role: a qualitative inquiry from the consultant's perspective - Kakabadse, Nada K.; Louchart, Eddy; Kakabadse, Andrew P. (Emerald Group Publishing Limited, 2006)
Many criticisms questioning the role and the efficiency of business consultants have been addressed. However, although a great deal of research has been carried out on business consultancy, little has been written on business consultancy from the consultant's viewpoint. In order to gain a detailed view of the situation from an internal consultant's perspective, an investigation of how business consultants perceive their role and contribution within their clients' organisations was undertaken. Drawing on different perspectives, this study aims to demystify the role of business consultants, and to ascertain how they perceive their role within their clients' organisations.
Keywords: Learning organisations; Management consultancy; Qualitative research; Skills